Sinkhole risk mapping and early warning: the case of Camaiore (Italy) - Intrieri, Emanuele; Confuorto, Pierluigi; Bianchini, Silvia; Rivolta, Carlo; Leva, Davide; Gregolon, Samuele; Buchignani, Vincenzo; Fanti, Riccardo (Frontiers in Earth Science, 2023)
Introduction: Sinkholes are ground collapses that can cause significant damage to infrastructure and buildings. Part of the risk represented by sinkholes is related to their abruptness and the difficulty in spotting in advance their exact location within a sinkhole-prone area. For this reason, urban planning informed by an accurate risk mapping and monitoring is one of the most effective ways to reduce the risk. Methods: In this study, we propose a two-folded procedure based on the examination of ground displacement data measured by a ground-based interferometric radar and on the generation of a sinkhole risk zonation map. We examined 11 years’ worth of ground displacement data measured by a ground-based interferometric radar to search for sinkhole precursors. The analysis was based on averaged displacement time series retrieved from high-coherence pixels scattered around Camaiore, Italy, a test site where a catastrophic sinkhole occurred in 1995. To generate a sinkhole risk map, we evaluated the susceptibility map as derived from a set of predisposing environmental parameters, the vulnerability derived from the thickness of the sedimentary cover that can be linked to the abruptness of the collapse, and the value of the elements at risk from the Italian Real Estate Market Observatory integrated with land cover information for the non-built up areas. Results: The analysis of ground displacement data revealed that Camaiore had not experienced subsidence relatable to incoming sinkholes in the monitored period. However, few cm of vertical movements, which are well correlated with water table oscillations, have been measured and are expected to be of the same order of magnitude of sinkhole precursor deformations. This implies that a phenomenon of the size and velocity of the 1995 event could have likely been detected before its final collapse. The sinkhole risk map identified specific areas that should be closely monitored using in situ and remote sensing instrumentation. Discussion: The sinkhole risk zonation map generated in this study can be used to inform urban planning and risk management strategies. The study also shows the potential of ground-based interferometric radar to detect sinkhole precursors and the importance of integrating different mitigation approaches. Overall, this study can provide insights for sinkhole risk assessment and management in sinkhole-prone areas.